Efficiency of Palm Oil Companies in Indonesia: A DEA Approach - M. Khairul Anam; Suhartini Suhartini (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
The purpose of this study was to investigate technical, allocative, cost and scale efficiency of palm oil companies in Indonesia. The data used cross sectional data on Indonesian Manufacturing Industries that were collected in the annual surveys by Indonesia’s Central of Statistics/BPS for 2015 which is registered under KBLI code 10431. Data envelopment analysis (DEA) is a nonparametric method in operations research and economics for the estimation of production frontiers. It is used to empirically measure productive efficiency of decision making units (DMUs). The input of the palm oil production system are capital, labor, materials, land and energy. While output include industrial product in terms of CPO/PKO and biogas. The finding shows that Riau Island, North Sulawesi and Papua have high score of efficiency in terms of TE, AE, CE and SE, while West Java and Banten province at low level in terms of cost and allocative efficiency. Nevertheless, on nationwide the score of allocative and cost efficiency still low. Hence, all the input efficiencies still need to be improved, and also reduce cost of production. Beside that, the companies should make an improvement by enhancing management capabilities and improving allocation efficiency.